2014
DOI: 10.1088/1742-5468/2014/10/p10004
|View full text |Cite
|
Sign up to set email alerts
|

From conformal to volume law for the entanglement entropy in exponentially deformed critical spin 1/2 chains

Abstract: An exponential deformation of 1D critical Hamiltonians gives rise to ground states whose entanglement entropy satisfies a volume-law. This effect is exemplified in the XX and Heisenberg models. In the XX case we characterize the crossover between the critical and the maximally entangled ground state in terms of the entanglement entropy and the entanglement spectrum.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(154 citation statements)
references
References 39 publications
(70 reference statements)
4
147
1
Order By: Relevance
“…It has been shown that a strong correlation in the noise can change the universality class and induce Griffiths singularities [15]. In some cases, inhomogeneous non-random couplings can present very large entanglement, for example, if they decay exponentially from the center, they give rise to the rainbow phase, in which singlets extend concentrically [19][20][21]. Thus, it is natural to ask about the possible fixed points of the SDRG when we consider ensembles of couplings which present long-range correlations, but are still random.New candidates to fixed points can be found by observing the statistical mechanics of the secondary structure of RNA [22].…”
mentioning
confidence: 99%
“…It has been shown that a strong correlation in the noise can change the universality class and induce Griffiths singularities [15]. In some cases, inhomogeneous non-random couplings can present very large entanglement, for example, if they decay exponentially from the center, they give rise to the rainbow phase, in which singlets extend concentrically [19][20][21]. Thus, it is natural to ask about the possible fixed points of the SDRG when we consider ensembles of couplings which present long-range correlations, but are still random.New candidates to fixed points can be found by observing the statistical mechanics of the secondary structure of RNA [22].…”
mentioning
confidence: 99%
“…Returning to expression (19) we can state that |D 0l | 2 = |β l | 2 and, approximately, U kl ≈ δ lk , thus obtaining Notice that the local occupation (and, therefore, the local temperature) is related to the form of the orbitals and the energy content at the site to which the detector is attached. The long-term average occupation always depends quadratically with the coupling constant, n 0 ∼ g 2 , for low enough g. Let us remark again that in order to define a proper local temperature one should always take the limit g → 0.…”
Section: Single Qubit Detectorsmentioning
confidence: 98%
“…A. The rainbow system As our physical system, we have chosen the rainbow system [25][26][27], a 1D inhomogeneous fermionic hopping system which presents volumetric entanglement between its left and right halves. It can be described on an open chain through the following Hamiltonian,…”
Section: Numerical Experimentsmentioning
confidence: 99%